Nigeria’s Image, Democracy and Foreign Policy, 1999-2007 (Asian Journal of Social Science Studies, 2018)
Nigeria’s image was negative prior the return of democracy in 1999. The major cause of this was the long period of military rule which not only dismantled democratic institutions, but made Nigeria a pariah State as a result of corruption and draconian policies. The protracted military rule led to plethora of sanctions which led to hardship on the populace. The return to democratic governance reinvented the State and ushered in diplomatic shuffles which culminated to the eliminating of the sanctions which eventually readmitted the country into global reckoning. This study reviews Nigeria’s image, democracy and foreign policy, 1999–2007, adopting content analysis in the scrutiny of our data and political economy perspectives as a paradigm for our analysis. It recommends effective Executive – Legislative Collaboration as a panacea for achieving effective and stable foreign policy.